Framework for analyzing online asynchronous discussion by integrating content analysis and social network analysis [electronic resource] - Erlin, 1969-; Norazah Yusof; Azizah Abdul Rahman, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (2011)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2011